ПРОБЛЕМА РАЗРУШЕНИЯ АРИДНЫХ РАВНИН ДОРОЖНОЙ И ВОЕННОЙ ДИГРЕССИЕЙ - Чичагов В.П. (My University, 2005)
Author suggests and investigates the new in the earth's sciences problem of arid plains destruction due to hostilities and dirt roads exploitation. The history of such man-made changes since the early bronze age are discussed. In the evolution of war and road destruction there are calm (peace) periods and catastrophic (war) ones. The impact of hostilities on the natural environment and relief of arid plains is enormous. The significant natural instability and vulnerability are incident to arid plains: no linear disruption does happen without consequences. Up to 17 active exogenic processes may take part in the development of linear destruction. Their integral effect may result in the formation of anthropogenic plains or in the creation of dissected relief.
Keywords: 551.438.5:625.74